2008
DOI: 10.3201/1408.080068
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Circulation of European Bat Lyssavirus Type 1 in Serotine Bats, Spain

Abstract: To determine the presence of European bat lyssavirus type 1 in southern Spain, we studied 19 colonies of serotine bats ( Eptesicus isabellinus), its main reservoir, during 1998–2003. Viral genome and antibodies were detected in healthy bats, which suggests subclinical infection. The different temporal patterns of circulation found in each colony indicate independent endemic circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
(26 reference statements)
9
35
0
1
Order By: Relevance
“…With more than 4000 oropharyngeal swabs and 1200 blood samples tested by RT-PCR and RFFIT, respectively, this is one of the most extensive active bat rabies surveillance studies ever conducted in Europe. While in several European studies no EBLVspecific RNA was detected in oropharyngeal swabs [6], we found seven oropharyngeal swab samples positive for EBLV-1 by RT-PCR which is in accordance with previous reports from Spain, UK and Switzerland [13,20,24,25]. The majority of RT-PCR-positive results were associated with E. serotinus bats, the natural reservoir host of EBLV-1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With more than 4000 oropharyngeal swabs and 1200 blood samples tested by RT-PCR and RFFIT, respectively, this is one of the most extensive active bat rabies surveillance studies ever conducted in Europe. While in several European studies no EBLVspecific RNA was detected in oropharyngeal swabs [6], we found seven oropharyngeal swab samples positive for EBLV-1 by RT-PCR which is in accordance with previous reports from Spain, UK and Switzerland [13,20,24,25]. The majority of RT-PCR-positive results were associated with E. serotinus bats, the natural reservoir host of EBLV-1.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, repeated detection of viral RNA in saliva swabs from recaptured serotine bats (E. serotinus) was not observed. In Spain, an initially EBLV-1-positive E. isabellinus was negative on recapturing [20], thus supporting observations in experimentally infected serotine bats [41,42]. However, unlike in other studies, not only serotine bats but also a single Natterer's bat and Western barbastelle bats tested positive for EBLV-1-specific RNA.…”
Section: Discussionsupporting
confidence: 74%
“…EBLV-1 and EBLV-2 have been shown to have a specific association with the Serotine bat (Eptesicus serotinus and Eptesicus isabellinus) (Vazquez-Moron et al, 2008;Picard-Meyer et al, 2004b) and the species of Myotis bats (Myotis daubentonii and Myotis dascyneme), respectively (Whitby et al, 2000;Johnson et al, 2003;Harris et al, 2006), whereas rabies cases due to EBLVs in other bat species have only occasionally been reported (Müller et al, 2007). West Caucasian bat virus (WCBV), a recently ratified member of the lyssavirus genus with distinct genetic and biological properties, was isolated from a Schreiber's long-fingered bat (Miniopterus schreibersii) on the European side of the Caucasus mountain range (Kuzmin et al, 2005).…”
Section: Recommendations On Bat Rabies Surveillancementioning
confidence: 99%
“…We investigated these hypothetical genetic/spatial associations at two different geographic scales: (1) between Iberian and geographically disjunct African populations to evaluate the role of the Straits of Gibraltar as an isolating barrier; and (2) among maternity colonies at local scales to assess the degree of genetic structure and gene flow caused by female movements. Finally, we discuss the results in light of the rabies circulation pattern recently described (Vázquez-Moró n et al, 2008) between these bat colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Both Eptesicus species have a crucial role as reservoirs of the most common European bat rabies strain EBLV-1 (Pö tzsch et al, 2002), whose circulation dynamics and pathogenesis are currently being investigated (Vázquez-Moró n et al, 2008). Understanding this virus' population dynamics, critical for designing appropriate epidemiological control measures for rabies, requires an understanding of the regional structure, population dynamics and genetic connectivity present in bat host populations.…”
Section: Introductionmentioning
confidence: 99%